Penerapan Metode Content-Based Filtering pada Sistem Rekomendasi - Tegar Ridwansyah; Betty Subartini; Sisilia Sylviani (Mathematical Sciences and Applications Journal, 2024)
Content-based filtering is one of the recommendation system methods that provides recommendations based on the similarity of attributes or items preferred by users. Several researchers in various fields have used content-based filtering in their research. This paper describes several studies in various fields using content-based filtering to solve the problems faced in their research. From these studies, the researchers revealed that the use of content-based filtering can produce simple and efficient recommendations and its application can increase the revenue of a business.